Compositional Flux Within the Intestinal Microbiota and Risk for Bloodstream Infection With Gram-negative Bacteria. (24th January 2020) - Stoma, Igor; Littmann, Eric R; Peled, Jonathan U; Giralt, Sergio; van den Brink, Marcel R M; Pamer, Eric G; Taur, Ying
Abstract: Background: Gram-negative bloodstream infections (BSIs) represent a significant complication facing allogeneic hematopoietic cell transplant (allo-HCT) recipients, as a result of intestinal translocation during neutropenia. In this study we sought to better understand how the composition of the intestinal microbiota is connected to risk of gram-negative BSIs, expanding on our prior work in these patients. Methods: Fecal specimens were collected from recipients of allo-HCT and analyzed using 16S ribosomal RNA gene sequencing. Samples and clinical data extending from the pretransplant conditioning period through stem cell engraftment were used in the analysis. Intestinal domination (relative abundance ≥ 30%) by gram-negative bacteria was used as predictor of gram-negative BSI using Cox proportional hazards modeling. Further analysis of microbiota composition was performed at the genus level. Results: Seven hundred eight allo-HCT subjects were studied (7.5% developed gram-negative infection), with 4768 fecal samples for analysis. Gram-negative intestinal domination was associated with subsequent BSI, which was observed overall and individually at the genus level: Escherichia, Klebsiella, Enterobacter, Pseudomonas, and Stenotrophomonas. Fluoroquinolone prophylaxis was associated with decreased BSI and intestinal colonization by gram-negative microbes. In fluoroquinolone-prophylaxed patients, Escherichia coli was more frequently observed as breakthrough, both in terms of intestinal colonization and BSIs, compared with nonprophylaxed patients. Initial colonization by members of Ruminococcaceae and Bacteroidetes were associated with protection against gram-negative BSI. Conclusions: Gram-negative intestinal colonization is highly predictive of BSI in the setting of allo-HCT. Fluoroquinolones appear to reduce these infections by influencing gut colonization. Abstract : In this study, the intestinal microbiota and risk of gram-negative bloodstream infections was studied in patients undergoing allogeneic hematopoietic cell transplantation, during neutropenia. Expansion and domination by gram negatives occur in these patients and are predictive of bloodstream infection.